PERBEDAAN KORELASI GLUKOSA DARAH PUASA PENDERITA DM DENGAN HbA1c METODE ENZIMATIK DAN HPLC DI RUMAH SAKIT ADVENT BANDUNG - Widianingrum, Indriati; Kurnaeni, Nani (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Palembang, 2024)
Background: Diabetes Mellitus (DM) is one of the diseases that many people in the world suffer from today, its development is very worrying because it is one of the diseases that can cause death. One of the tests requested by the doctor is the HbA1c parameter, so far at Advent Bandung Hospital using the enzymatic method. The aim of this study was to look at the differences in the correlation between fasting blood glucose examination results and HbA1c levels using enzymatic and HPLC methods. Methods: The research method currently used is descriptive and was carried out at the Clinical Pathology Laboratory Installation at Bandung Adventist Hospital in November with a total of 30 patients suffering from diabetes. Results: The results were analyzed using the SPSS version 25 application. Tested with a normality test followed by a correlation test, the results showed a strong relationship between fasting blood glucose levels and HbA1c levels by the enzymatic and HPLC methods, from both methods the results of the HbA1c examination were between the enzymatic and HPLC methods. there is no significant difference. This means that both methods can be used to check HbA1c at the Bandung Adventist Hospital. HbA1c, this is because the two methods do not have significant differences and have high accuracy. Keywords : Diabetes, Fasting Blood Glukoce , HbA1c Method Enzymatic and HPLC